2022
DOI: 10.1101/2022.10.06.22280777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Treating intrusive memories after trauma in healthcare workers: a Bayesian adaptive randomised trial developing an imagery-competing task intervention

Abstract: Intensive care unit (ICU) staff continue to face recurrent work-related traumatic events throughout the COVID-19 pandemic. Intrusive memories (IMs) of such traumatic events comprise sensory image-based memories. Harnessing research on preventing IMs with a novel behavioural intervention on the day of trauma, here we take critical next steps in developing this approach as a treatment for ICU staff who are already experiencing IMs days, weeks, or months post-trauma. To address the urgent need to develop novel me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The number of times a memory intrudes can be counted and recorded (say, in a diary). A reduction in the probability of the number of intrusions over a given time period is a primary outcome measure for recent intervention development [3032]. Our stochastic framework can be used to simulate different treatment interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of times a memory intrudes can be counted and recorded (say, in a diary). A reduction in the probability of the number of intrusions over a given time period is a primary outcome measure for recent intervention development [3032]. Our stochastic framework can be used to simulate different treatment interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory and clinical studies have shown that treatment interventions with a cognitive task can reduce the propensity of the intrusive memories to (re)consolidate following a memory reminder cue soon after a trauma [2831,45]. Furthermore, there is emerging evidence for the success of these interventions when delivered at later time intervals since the trauma occurred [32,46,47]. Here, we have shown that delivering multiple doses or different (task) interventions is likely to achieve greater marginal gains in reducing the probability of intrusive memories reconsolidating than simply increasing the strength of a single-task intervention.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment, the event becomes available to declarative memory without evoking the strong pathological emotion characteristic of PTSD. Also, within the behavioural interventions, playing Tetris after a memory reminder cue reduced traumatic memory intrusions in traumaexposed patients [98] and intensive care unit staff [99], two subpopulations with increased vulnerability to disease onset [100].…”
Section: Disrupting Maladaptive Memoriesmentioning
confidence: 99%
“…The number of times a memory intrudes can be counted and recorded (say, in a diary). A reduction in the probability of the number of intrusions over a given time period is a primary outcome measure for recent intervention development [30,31,32]. Our stochastic framework can be used to simulate different treatment interventions.…”
Section: Simulating Different Treatment Interventionsmentioning
confidence: 99%
“…Laboratory and clinical studies have shown that treatment interventions with a cognitive task can reduce the propensity of the intrusive memories to (re)consolidate following a memory reminder cue soon after a trauma [29,30,31,45]. Furthermore, there is emerging evidence for the success of these intervention when delivered a later time intervals since the trauma occurred [32,46,47]. Here, we have shown that delivering multiple doses or different (task) interventions is likely to achieve greater marginal gains in reducing the probability of intrusive memories reconsolidating than simply increasing the strength of a single task intervention.…”
Section: Task Interventions Can Influence Suites Of Memory States Fol...mentioning
confidence: 99%